Bimbingan Interaksi Sosial Anak Kelainan Bicara di Panti Sosial Bina Serumpun Dinas Sosial Provinsi Kepulauan Bangka Belitung - Ririh Agung; Muhammad Sholeh Marsudi (Department of Islamic Guidance and Counseling, 2021)
This paper aims to discuss the social interaction guidance of speech impaired children at the Bina Serumpun Social Institution of the Bangka Belitung Islands Social Service, which includes the concept of implementation and the inhibiting factors of social interaction guidance for speech impaired children. The type of research used is field research with qualitative descriptive methods. The results of the discussion show that the concept of implementing guidance for children with speech disorders is through the stages of assessment, determination of therapists, implementation of therapy, and evaluation. Inhibiting factors from the interaction of children with speech disorders include the social and emotional environment of children that are not supportive, understanding of parents, lack of socialization, and barriers to focusing the child's attention.